Renal health benefits and therapeutic effects of parsley (Petroselinum crispum): a review - Alobaidi, Sami (Frontiers in Medicine, 2024)
Parsley (Petroselinum crispum) has been used in traditional medicine for its diverse health benefits, and recent research highlights its potential in promoting renal health due to its bioactive compounds. This review focuses on evaluating the renal health benefits and therapeutic effects of parsley, addressing the growing interest in natural interventions for kidney-related conditions. It aims to consolidate existing evidence while identifying research gaps to support parsley’s integration into renal health management. A systematic review of scientific databases was conducted, identifying relevant studies on parsley’s biochemical properties, including flavonoids, phenolic acids, terpenoids, and essential oils, which contribute to antioxidant, anti-inflammatory, diuretic, and nephroprotective effects. Animal studies demonstrated reductions in oxidative stress, improvements in metabolic biomarkers, and enhanced renal function, while limited human studies revealed modest improvements in urinary composition and renal health markers. However, parsley’s safety profile, particularly at high doses, requires further investigation, including potential herb-drug interactions and safety during pregnancy. This review highlights parsley’s therapeutic potential as a natural agent for renal health and underscores the need for robust clinical trials, long-term safety evaluations, and standardized methodologies to validate its clinical significance.